Effectiveness of CenteringPregnancy on Breastfeeding Initiation Among African Americans: A Systematic Review and Meta-analysis. Issue 2 (April 2018) - Robinson, Karen; Garnier-Villarreal, Mauricio; Hanson, Lisa
Abstract : While breastfeeding initiation rates for African American mothers are low, an innovative model of group prenatal care, CenteringPregnancy, holds promise to increase breastfeeding rates. The aim of this systematic review and meta-analysis was to examine the effects of CenteringPregnancy versus individual prenatal care on breastfeeding initiation among African American mothers. Using a systematic approach and PRISMA guidelines, 4 electronic databases were used to search the literature. English-language studies, comparing CenteringPregnancy and individual prenatal care, including African American participants, and specifying breastfeeding initiation as an outcome were screened for inclusion. Study strength and quality were assessed and 7 studies were systematically reviewed and meta-analyzed. Participation in CenteringPregnancy increased the probability of breastfeeding initiation by 53% (95% confidence interval = 29%-81%) (n = 8047). A subgroup analysis of breastfeeding initiation among only African American participants was performed on 4 studies where data were available. Participation in CenteringPregnancy increased the probability of breastfeeding initiation by 71% (95% confidence interval = 27%-131%) (n = 1458) for African American participants. CenteringPregnancy is an effective intervention to increase breastfeeding initiation for participants, especially for African Americans. To close the racial gap in breastfeeding initiation, high-quality research providing specific outcomes for African American participants in CenteringPregnancy are needed.